Invasive Plants Differentially Impact Forest Invertebrates, Providing Taxon-Specific Benefits by Enhancing Structural Complexity - Landsman, Andrew P.; Schmit, John Paul; Matthews, Elizabeth R. (Frontiers in Ecology and Evolution, 2021)
Exotic plant species often negatively affect native herbivores due to the lack of palatability of the invading plant. Although often unsuitable as food, certain invasive species may provide non-nutritional ecological benefits through increased habitat structural complexity. To understand the potential for common invasive forest plant species of the eastern United States to benefit invertebrate communities, we examined the functional and taxonomic community composition of forest insects and spiders in long-term monitoring plots that contained invasive plant species. The extent of invasive plant species ground cover significantly altered spider community composition as categorized by hunting guild. Areas with higher invasive herbaceous and grass cover contained a higher abundance of space web-weaving and hunting spiders, respectively. Spider species richness and total invertebrate abundance also increased with greater invasive grass cover. Still, these trends were driven by just two invasive plant species, garlic mustard and Japanese stiltgrass, both of which have previously been shown to provide structural benefits to native invertebrate taxa. While these two species may improve the structural component of understory forest habitat, many invertebrate groups were not significantly correlated with other prevalent invasive plants and one species, mock strawberry, negatively affected the abundance of certain insect taxa. Particularly in forests with reduced native plant structure, invasive plant management must be conducted with consideration for holistic habitat quality, including both plant palatability and structure.